Exploratory examination of the association between physical-mental multimorbidity and physical activity in children - Bedard, Chloe; Timmons, Brian W.; Ferro, Mark A. (Frontiers in Pediatrics, 2023)
Children with physical illnesses often experience co-occurring mental illness (known as multimorbidity; MM) and it is currently unknown if MM is associated with physical activity (PA) and if the association differs between internalizing and externalizing disorders. Therefore, the aim of this study was to examine the association between MM and PA. Baseline data from the Multimorbidity in Children and Youth Across the Life Course (MY LIFE) cohort was used. MY LIFE is an ongoing prospective study that follows children ages 2 to 16 years with a chronic physical illness and measures PA using accelerometry and mental illness using the Mini International Neuropsychiatric Interview for Children and Adolescents. 140 children (53.2%) provided valid accelerometer data. Children with internalizing disorders recorded less light (B=-5.87), moderate (B=-1.82), and vigorous PA (B=-1.93) and fewer days meeting PA guidelines (Exp(B)=0.73) and those with externalizing disorders recorded more light (B=4.85), moderate (B=1.78), and vigorous PA (B=2.41) and more days meeting PA guidelines (Exp(B)=0.06). However, only the association between internalizing disorder and days meeting PA guidelines was statistically significant. This study provides preliminary evidence that children with MM may accumulate less PA depending on the type of mental illness they experience.